Thermal spa treatments and benefits perceived by users of Cró and Carvalhal spa for dermatological purpose - Pereira, Ana; Fonseca, Cecília; Coutinho, Paula; Cruz, Agostinho; Araujo, André RTS (Tourism and Hospitality International Journal, 2023)
Thermalism constitutes one touristic product highly recognized for its enormous potential regarding the exploitation of regional endogenous resources with noteworthy economic impacts for local communities. In the last decades, an important change occurs in the clinical use of thermal water for the treatment of several dermatological diseases, mainly due to the increase of knowledge and research, that highlighting the beneficial effects of these waters to support, improve or treatment of different disorders.The aim of present study was the evaluation of the benefits of thermal treatments on different skin diseases perceived by users (N=74) with dermatological diseases, of the thermal spas of Cró and Carvalhal, from the central region of Portugal. Most of the participants claim to have knowledge of the dermatological therapeutic benefits/properties of the thermal waters (78.4%), highlighting the healing effect, moisturizing and anti-itching properties. Although a small number of participants meet some secondary effects (25.7%), tiredness and drowsiness were the more often referred. The thermal treatment most frequently used were immersion bath (49.3%), partial/general shower-massage (17.8%), thermal swimming-pool (15.8%) and circular shower (8.2%). Reduction of erythema (27.8%), flaking (25.6%) and pruritus (25.6%) were the most valuated improvements on skin conditions referred by participants.It was concluded that thermal spas users claim to have knowledge about the effectiveness and safety of thermal waters in skin pathologies treatment. Therefore, it is envisioned that growing well-being modality of thermalism together with the medicinal one, it will certainly be rendered in a high economic impact in this touristic market.